Vitamin B12 and folate deficiency: should we use a different cutoff value for hematologic disorders?. (24th October 2013) - Toprak, B.; Yalcın, H. Z.; Colak, A.
Summary Introduction Anemia and macrocytosis are well‐defined expected hematologic findings of vitamin B12 and folate deficiency; however, some previous studies did not show a significant association of subnormal B12 with anemia and macrocytosis. Methods We retrospectively analyzed 17 713 laboratory patient records to evaluate vitamin B12 and folate levels in relation to anemia and macrocytosis. Results In an age‐ and sex‐adjusted logistic regression model, low B12 status but not marginal B12 status was significantly associated with anemia [ORs respectively, 1.291 (95% CI, 1.182–1.410), 1.022 (95% CI, 0.943–1.108)] and macrocytosis [ORs, respectively, 3.853 (95% CI, 3.121–4.756), 1.031 (95% CI, 0.770–1.381)]. Also low folate status but not marginal folate status was significantly associated with anemia [adjusted ORs, respectively, 1.819 (95% CI, 1.372–2.411), 1.101 (95% CI, 0.931–1.301)] and macrocytosis [adjusted ORs, respectively, 2.945 (95% CI, 1.747–4.965), 1.228 (95% CI, 0.795–1.898)]. Conclusion Our results show that increased anemia and macrocytosis are observed at values below commonly used B12 lower‐reference thresholds. Determining a hematologic cutoff value may help physicians in clinical practice.